Tsunami Susceptibility Analysis in Coastal Area Petanahan District, Kebumen Regency - Fajar Aniq Safira; Chatarina Muryani; Gentur Adi Tjahjono (Jambura Geoscience Review, 2022)
Petanahan sub-district has three villages directly adjacent to the sea: Karangrejo Village, Karanggadung Village, and Tegalretno Village. This study aims to analyze the level of tsunami susceptibility in the coastal area of Petanahan District in the Kebumen Regency. Analysis of the level of tsunami susceptibility using assessment methods, weighting, and map overlays using tsunami hazard parameters, including elevation, slope, land use, distance from the shoreline, and distance from rivers. Then the Weighting of the Tsunami Vulnerability Level uses the formula N = Bi X Si, where Bi is the weight on each criterion, and Si is a score on each criterion. The weighting results are then divided into five classes, very low, low, medium, high, and very high. The results of this study indicate that the tsunami hazard in a coastal area of Petanahan Regency consists of a very high class (93.904 ha/8.33%), a high class (567.804/50.35%), and a medium class of (465.962 ha/41.32%). The results of this research on the vulnerability to tsunamis can be used by the community, especially in the research area, to increase preparedness in dealing with tsunami disasters. At the same time, the Government can take policies in carrying out disaster risk reduction activities of a tsunami, especially in the research area.